Migração negra interna e identidade no quilombo do América uma contribuição - SANTIAGO, Ketno Lucas (Universidade Federal do Pará, 2020)
This research is the result of a bibliographical review on the migration category, whose focus is the black migration, as well as the studies about the cultural identity in the Quilombola community of America, located in the city of Bragança, State of Pará The main objective is to locate studies that deal with issues such as migration, black migration and forced and internal migration. Articulate the migratory movements with the studies developed on cultural issues produced by the quilombola population, as well as indicate indicatives for the constitution of an identity vision in the formation of these traditional peoples. Methodologically, the path covered is a historiographical one, through a bibliographical review, identifying theories that contributed to establish a dialogue between the suggested categories. Initially the results indicate that the arrival of Africans in Brazil and in the Bragantina Amazon Region occurred through a process of forced black migration and internal migration. The economic factor is the predominant hypothesis, which motivated the displacement of this population. Self-identification is a vision of belonging, presents some evidence of the identity and cultural character of the remaining quilombolas. We conclude that it was possible to identify some authors that approach on the issue of migration and its variations, authors that dialogue with the thematic identity and culture. It was possible to identify, in a preliminary way, that the cultural identity of the quilombola population has traits due to their belonging and resistance against the forms of oppression and violation of their rights as inhabitants of Quilombo of America over the years.